PROBLEMS IN THE CONSERVATION AND EXPLOITATION OF OBJECTS OF CULTURAL HERITAGE: PROBLEMS IN THE CONSERVATION AND EXPLOITATION OF OBJECTS OF CULTURAL HERITAGE - Ivanov, Sabin (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The topic of preservation of cultural heritage is very important and is an integral part of National Security. It is up-to-date and timely. Its significance is determined by the scale and intensity of criminal attacks on cultural heritage, which have caused an increase in the need to update the system of measures to safeguard cultural values and overcome the underestimation of the protection of cultural heritage as a national security factor.